A Freestanding Flexible Single‐Atom Cobalt‐Based Multifunctional Interlayer toward Reversible and Durable Lithium‐Sulfur Batteries. Issue 3 (27th January 2020) - Li, Yiju; Zhou, Peng; Li, Hui; Gao, Tingting; Zhou, Lei; Zhang, Yelong; Xiao, Ni; Xia, Zhonghong; Wang, Liang; Zhang, Qinghua; Gu, Lin; Guo, Shaojun
Abstract: The development of Li‐S batteries is greatly hindered by the polysulfide shuttling and sluggish sulfur redox kinetics, leading to low utilization of active materials and rapid capacity decay. Herein, a freestanding multifunctional interlayer, prepared by layer‐by‐layer assembling of the single‐atom cobalt‐anchored nitrogen‐doped carbon nanosheets (NC@SA‐Co) and dual network of carbon nanotube‐cellulose nanofiber (CNT‐CNF) hybrid, is proposed to effectively enhance the polysulfide immobilization and sulfur redox kinetics. The conductive CNT network acts as the physical barrier to confine the polysulfide diffusion and to facilitate the reuse of polysulfides. The oxygen‐group‐terminated CNF network allows the hopping of Li + ion and suppresses the polysulfide crossover due to the strong electrostatic repulsion. Moreover, it is demonstrated that the 2D NC@SA‐Co with numerous well‐defined single sites of Co–N4 can effectively serve as an electrocatalyst to boost the reversible reaction of polysulfides. As a result, the assembled Li‐S batteries with the multifunctional interlayer deliver a high reversible specific capacity of 1160 mAh g −1 at 0.1 C and an ultralow capacity decay of 0.058% per cycle over 700 cycles. Even with a high sulfur loading of 7.2 mg cm −2, a high areal capacity of 8.3 mAh cm −2 can be achieved. Abstract : A freestanding and flexible multifunctional interlayer is designed using a facile layer‐by‐layer assembling method to enhance the confinement of polysulfides and accelerate sulfur redox kinetics. The assembled Li‐S batteries with the multifunctional interlayer display favorable rate performance and long‐term cyclic stability. This work provides an interfacial strategy to effectively regulate the migration and reaction of sulfur species.